Karakteristik Tindak Pidana Pemilu (Pemilihan Umum) dan Opsi Pembagianya - Kholilur Rahman; M Djalil; Jamil Jamil (JURNAL BELO, 2022)
Election Crimes are criminal acts with administrative character (administrative penal law) because they threaten criminal sanctions for administrative of administrative crime is guided by the ultimum remedium principle, namely using criminal sanctions as the last alternative after prioritizing administrative sanctions. However, because criminal offenses ini elections have different destructive powers against elections, there should be a clear classification between each election crime. This means that even though they are included in the administrative penal law category, not all of them adhere to the ultimum remedium principle. This papare will discuss the characteristics of election crimes and aims to propose a clustering of election crimes based on certain measures, so that in their enforcement it is not gereralized between different criminal offenses. This paper uses a normative research method with conceptual opproach and statuta approach.